2018
DOI: 10.48550/arxiv.1811.08756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burden in Henselian Valued Fields

Abstract: In the spirit of the Ax-Kochen-Ershov principle, we show that in certain cases the burden of a Henselian valued field can be computed in terms of the burden of its residue field and that of its value group. To do so, we first see that the burden of such a field is equal to the burden of its RV-sort. These results are generalizations of Chernikov and Simon's work in [CS16].In [She90], Shelah started to classify first order theories by elaborating a hierarchy of combinatorial properties of families of definable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In [19,Theorem 7.6] Chernikov proved that a henselian valued field of equicharacteristic zero in the L ac language is N T P 2 if and only if its residue field is N T P 2 . Later in [20,Theorem 3.11] P. Touchard proved that if K = (K, k, Γ, ac, res, v) is a henselian valued field of equicharacteristic zero then bdn(K ac ) = bdn(k) + bdn(Γ), where bdn(X) is the burden of the definable set X as defined in [20,Definition 1.12]. He also showed that if a valued field of equicharacteristic zero is considered in the language L then bdn(K) = max n≥0 (bdn(k × (k × ) n ) + bdn(nΓ)), therefore a henselian valued field of equicharacteristic zero is N T P 2 if and only if its residue field is N T P 2 .…”
Section: Domination By the Residue Field And The Value Group In The L...mentioning
confidence: 99%
“…In [19,Theorem 7.6] Chernikov proved that a henselian valued field of equicharacteristic zero in the L ac language is N T P 2 if and only if its residue field is N T P 2 . Later in [20,Theorem 3.11] P. Touchard proved that if K = (K, k, Γ, ac, res, v) is a henselian valued field of equicharacteristic zero then bdn(K ac ) = bdn(k) + bdn(Γ), where bdn(X) is the burden of the definable set X as defined in [20,Definition 1.12]. He also showed that if a valued field of equicharacteristic zero is considered in the language L then bdn(K) = max n≥0 (bdn(k × (k × ) n ) + bdn(nΓ)), therefore a henselian valued field of equicharacteristic zero is N T P 2 if and only if its residue field is N T P 2 .…”
Section: Domination By the Residue Field And The Value Group In The L...mentioning
confidence: 99%
“…When we do, this will be indicated to the reader with a superscript ⋆: Card ⋆ , bdn ⋆ , sup ⋆ etc. For more details, notably about the arithmetic of Card ⋆ , see [22,Section 1.1.3]). We will also use Rideau-Kikushi's terminology in [18,Annex A].…”
Section: Notation and Prerequisitesmentioning
confidence: 99%
“…We may assume the array of parameters to be mutually indiscernible. By Proposition 1.3 and elimination of the disjunction in inp-patterns (see for instance [22]), we may assume that every formula φ(x, b, c) with variable x ∈ V and parameters b ∈ V , c ∈ K is a conjunction of:…”
Section: Transfer Principles In Vector Spaces Relative To the Base Fieldmentioning
confidence: 99%
See 2 more Smart Citations